Phased array weather radar for heavy precipitation measurements with high resolution. Issue 2 (7th February 2021) - Ushio, Tomoo
Abstract: A new Phased Array Radar (PAR) system for meteorological application has been developed by Toshiba Corporation and Osaka University under a grant of NICT, and installed in Osaka University, Japan in 2012. The PAR system developed has the unique capability of scanning the whole sky with 100 m and 10 to 30‐second resolution up to 60 km. The system adopts the digital beam forming technique for elevation scanning and mechanically rotates the array antenna in azimuth direction within 10 to 30 seconds. The radar transmits a broad beam of several degrees with 24 antenna elements and receives the back scattered signal with 128 elements digitizing at each element. Then, by digitally forming the beam in the signal processor, the fast scanning is realized. After the installation of the PAR, SIP project has started to develop a new PAR with polarimetric capabilities.